The fast forward MBA in project management - Verzuh, Eric (Wiley, 2016)
Contents: For any professional responsible for coordinating projects among different departments, executive levels, or projects with technical complexity, this book clearly explains how to do it on time and on budget. From finding the right sponsor to clarifying objectives to setting a realistic schedule and budget projections, this book will help everyone better manage the relationships and process needed to get the project done. This fifth edition is updated to reflect changes in the business environment in the past few years including: Rewrites to connect to current events and trends. New case studies of project management in action (Hospital Enterprise Project Management Office and Washington State's Highway 99 tunnel). An updated chapter on engaging stockholders and the discipline of change management. Information on using Agile techniques for project scheduling. References to the PMP exam.